Teologi Kasih dalam Konseling Pastoral: Pendekatan Solusi untuk Kenakalan Remaja - Manurung, Haris Benaya; Hindradjat, Juliana (PT. Giat Konseling Nusantara, 2025)
Juvenile delinquency is one of the significant challenges faced by modern societies, including Indonesia. Factors such as lack of affection, family conflicts, and environmental influences are often the main causes of deviant behavior. This study aims to analyze the application of love theology in pastoral counseling as a solution-oriented approach to address juvenile delinquency. The study employs a qualitative literature review method by analyzing relevant academic journals and books. The findings indicate that love theology, focusing on unconditional acceptance, forgiveness, and active love, plays an essential role in guiding adolescents toward spiritual recovery and moral transformation. This approach is considered effective in building empathetic relationships, providing spiritual support, and creating space for sustained character development.